Missing, unreplaced teeth and risk of all-cause and cardiovascular mortality - Schwahn, Christian; Polzer, Ines; Haring, Robin; Dörr, Marcus; Wallaschofski, Henri; Kocher, Thomas; Mundt, Torsten; Holtfreter, Birte; Samietz, Stefanie; Völzke, Henry; Biffar, Reiner (International journal of cardiology, 2013)
A dentition of at least 20 teeth is associated with sufficient masticatory efficiency and is a stated health goal of the World Health Organisation. We examined whether subjects with missing, unreplaced teeth had an increased mortality risk. We used data prospectively collected from those participants in the population-based Study of Health in Pomerania who had fewer than 20 remaining teeth, resulting in a sample of 1803 participants with a median age of 64years. Of those, 188 subjects had 9 or more unreplaced teeth. During a median follow-up period of 9.9years, 362 subjects died, 128 of whom of cardiovascular causes. We found that having 9 or more unreplaced teeth was related to all-cause mortality (rate ratio 1.53, 95% CI: 1.11–2.10; adjusted for variables according to causal diagrams: remaining teeth, age, sex, education, income, marital status, partnership, and oral health behaviour) and cardiovascular mortality (rate ratio 1.94, 95% CI: 1.15–3.25). When adjusting not only for the variables according to causal diagrams but also for smoking, alcohol consumption, physical activity, obesity, hypertension, diabetes, and dyslipidemia, the rate ratio was 1.43 (95% CI: 1.05–1.96) for all-cause mortality and 1.88 (95% CI: 1.10–3.21) for cardiovascular mortality. A reduced, unrestored dentition is associated with increased mortality risk. Thus, clinicians and dietitians have a responsibility to consider individual chewing ability in nutritional recommendations.